1992
DOI: 10.1515/jbcpp.1992.3.3.253
|View full text |Cite
|
Sign up to set email alerts
|

Pinealectomy but not Melatonin Supplementation Affects the Diurnal Variations in 125I-Melatonin Binding Sites in the Rat Brain

Abstract: The distribution of melatonin binding sites in synaptosomal preparations from five brain areas of sham-operated and pinealectomized young male rats (maintained in a 14 h light: 10 h darkness cycle; lights on at 5.00 h) was recorded at 10.00, 18.00 and 24.00 h, 18 days after surgery, using 125I-melatonin as a probe. The densities of 125I-melatonin binding sites in the medulla-pons, hippocampus and hypothalamus of the pinealectomized rats, exhibited clear diurnal variations. However, the densities of binding sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 34 publications
3
9
0
Order By: Relevance
“…Only a partial overlap existed between the timing of peaks or troughs of melatonin binding sites and crests or nadirs in tissue melatonin content. In pinealectomized rats, the densities of 125 I-melatonin binding sites in the medulla-ports, hippocampus and hypothalamus also varied diurnally (Oaknin-Bendahan et al, 1992), as is also confirmed in the present report. However, the densities of binding sites in these brain areas at 18.00 h, were lower in the pinealectomized animals, but higher in the sham-operated rats than at the other times of day tested.…”
Section: Introductionsupporting
confidence: 91%
“…Only a partial overlap existed between the timing of peaks or troughs of melatonin binding sites and crests or nadirs in tissue melatonin content. In pinealectomized rats, the densities of 125 I-melatonin binding sites in the medulla-ports, hippocampus and hypothalamus also varied diurnally (Oaknin-Bendahan et al, 1992), as is also confirmed in the present report. However, the densities of binding sites in these brain areas at 18.00 h, were lower in the pinealectomized animals, but higher in the sham-operated rats than at the other times of day tested.…”
Section: Introductionsupporting
confidence: 91%
“…This dose-dependent inhibition was noticeable at the lowest concentration of melatonin tested, 10 nM, i.e. within the range of the circulating levels of melatonin in rodents (Oaknin-Bendahan et al, 1992) and, therefore, could be a physiologically relevant process. Moreover, the ectopic production of melatonin by a variety of tissues is a well characterized phenomenon (Ozaki and Lynch, 1976;Kvetnoy and Yuzhakov, 1993) and may lead to local concentrations of the hormone at least one order of magnitude higher than the circulating levels (Shaw et al, 1989).…”
Section: Discussionmentioning
confidence: 82%
“…In light of evidence that GABA A receptor-mediated 402 nature neuroscience • volume 2 no 5 • may 1999 currents in CA1 neurons in hippocampal slices (Fig. 1d), as previous studies have revealed the presence of melatonin-binding sites in these neurons 11 . To our surprise, potentiation of GABA A receptor-mediated currents by melatonin was not observed in any neurons tested in this region.…”
mentioning
confidence: 99%